MARKETING STRATEGY OF BROILER MEAT AT UD CHICKEN AL-KAROMAH - A.N., Widdyanto; Putri, B.R.T.; Suarta, G. (Jurnal Peternakan Tropika, 2024)
This study aims to analyze internal and external factors that can influence broiler meat marketing strategies, analyze the position of broiler meat businesses in the livestock industry, and recommend appropriate marketing strategies for broiler meat products. This research is a case study conducted at a chicken slaughterhouse in West Denpasar. This research was 332 conducted in April-June 2023. There were 43 respondents to this study, consisting of 35 household consumers, 5 industrial consumers, 2 policy holders (government), 1 academic respondent. The data sources used are primary data and secondary data. Data were collected through observation, in-depth interviews, interviews with the help of questionnaires, and related literature searches. The analysis in this study uses the following 1) IFE and EFE analysis; 2) IE analysis; 3) SWOT analysis; 4) QSPM analysis. The results of the IFE and EFE analysis in this study indicate that the position of the broiler business in the livestock industry is in cell IV of the IE matrix, which is included in the growth and development division with an intensive strategy of market penetration, market development, and product development. Based on the results of the SWOT and QSPM analysis, it was found that the priority strategy in broiler meat marketing was product differentiation with a TAS value of 2.98.